Technology and student motivation in online Learning based on socioeconomic background - Sarimah Surianshah; Suriani Hassan; Nurul Atika Sazana Jamin (Atlantis press, 2023)
This study examines the effects of technology commonly used by students on student motivation in online learning in Mathematics and Science based on socioeconomic status. We used a sample of 360 secondary students in both urban and rural areas of Sabah, Malaysia. A random sampling method was employed in data collection. This study used the two-stage least squares approach. Analysis of the student motivation model revealed significant differences between students from urban and rural schools. Also, with the availability of technology, students from low social backgrounds are more likely to have low motivation in digital learning, with the effects become pronounced when the endogeneity problem is addressed using intergenerational household socio-economic background variables. Findings from this study perhaps may provide policymakers with insight into a better technology or ICT applications that can increase student motivation levels and ultimately engagement in digital learning in Mathematics and Science, especially in the current Covid-19 crisis. Also, it may provide guidelines to households to provide better technology for better educational outcomes of their children.